Zirconium-containing fiber aerogel with isotropic pore structure as well as preparation method and application of zirconium-containing fiber aerogel
By introducing bubble cells into the fiber aerogel and foaming treatment, a zirconium-containing fiber aerogel with isotropic pore structure was prepared, which solved the insufficient strength of the existing fiber aerogel at high temperature and the difficulty in controlling the structure. The problem is that higher temperature resistance and applicability are achieved.
Patent Information
- Application Number
- CN202411573186.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The existing fiber aerogels have problems such as insufficient strength and difficult to regulate microstructure when used in high-temperature environments, which limits their expansion in the field of high-temperature applications.
By introducing bubble cells into the pre-foaming slurry, the bubbles are evenly distributed using foaming technology, and retained after freezing and heat treatment, a zirconium-containing fiber aerogel with isotropic pore structure was prepared.
It realizes the isotropic structure of fiber aerogel, improves the temperature resistance and mechanical properties of the material, and is suitable for filtration, sound absorption, heat insulation, and thermal insulation under a temperature environment of -196-1300℃.
Smart Images

Figure CN119431004A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a zirconium-containing fiber aerogel with an isotropic pore structure and a preparation method and application thereof, belonging to the technical field of fiber aerogel. Background Art
[0002] In recent years, with the rapid development of cutting-edge technologies such as aerospace science and defense industry, more and more requirements have been put forward for materials used under high temperature. Aerogel has many excellent properties. It has extremely low thermal conductivity, which can be as low as 0.012W / (m·K), large specific surface area, and high porosity, which can reach 90%. The interior of aerogel is almost completely occupied by air, which makes it have extremely low density, the lowest density can be as low as 1.6mg / cm 3 These excellent properties of aerogel enable it to be used for flame retardancy, heat insulation and sound absorption in high temperature environments, and can also be used to capture some particles.
[0003] The sol-gel method is a common method for preparing aerogels. For example, CN118147788A discloses ceramic fiber aerogels and their preparation methods and applications. CN114772637A discloses methods for preparing zirconium dioxide aerogels with different microscopic morphologies. However, the strength of the aerogels prepared by the sol-gel method is poor, and they are easily damaged in application scenarios with complex forces. The sol-gel preparation method also makes it difficult to control the microstructure inside the material, and the random structure further reduces the mechanical properties of the material. These situations severely limit the application of aerogel materials in high temperature environments. Fibers have the characteristics of flexibility, light weight, high strength, heat resistance, and self-support. Using them as the structural elements of aerogels can maintain the porous structure of aerogels, while also giving them additional flexibility, strength, and heat resistance. For example, Chinese patent CN115850786A discloses a method for preparing glass fiber aerogel, wherein ultrafine glass fibers are dispersed in a mixed solution of sodium alginate and calcium carbonate to obtain a hydrogel containing fibers, and then the hydrogel is immersed in an acetone acetic acid solution to react with calcium carbonate to obtain a porous structure, wherein the ultrafine glass fibers play a supporting role, and the glass fiber aerogel is obtained by natural air drying. The aerogel has a uniform structure and a large specific surface area of 42 m 2 / g, thermal conductivity is 0.031W / (m·K). Chinese patent CN115286357A discloses a method for preparing silica fiber aerogel. After silica fiber is prepared, silica fiber, tetraethyl silicate and oxalic acid are mixed to obtain silica fiber dispersion, and silica fiber aerogel is obtained by freeze drying. The separation efficiency of this fiber aerogel for sewage is more than 98%. Chinese patent CN109180213A discloses a method for preparing elastic ceramic fiber aerogel. A precursor solution is obtained by dissolving a polymer, a lithium source, a lanthanum source, a titanium source and a zirconium source in a first solvent, a nanofiber membrane is obtained by an electrostatic spinning method, and the nanofiber membrane is dispersed in a second solvent to obtain a nanofiber membrane dispersion. After curing, the second solvent is removed to obtain a nanofiber aerogel. This material has a three-dimensional interconnected network, unique flexibility and elasticity, a large specific surface area and a low volume density. However, none of the above-mentioned fiber aerogels can adapt to high-temperature operating conditions, and when using freeze-solidified fiber dispersions, ice crystal growth often produces directionality, which will bring about structural anisotropy and limit the application of the material.
[0004] Therefore, it is of great significance to develop aerogels with isotropic structures, expand the application fields of materials, and select fibers with better temperature resistance as structural elements to improve the temperature resistance of materials. Summary of the invention
[0005] In view of the above-mentioned state of the prior art, the inventors of the present invention have conducted in-depth and extensive research in the field of aerogels and found that the problem of anisotropy of fiber aerogels can be solved by introducing pores into the pre-foamed slurry using foaming technology, and the bubbles are evenly distributed in the slurry, which are retained after curing and dried to obtain porous fiber aerogels. Zirconium-containing fibers are used as structural elements, and the temperature resistance of the material is improved compared to the reported glass fibers and ceramic fibers. The present invention is completed based on the above-mentioned findings.
[0006] Therefore, one object of the present invention is to provide a zirconium-containing fiber aerogel having an isotropic pore structure.
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned zirconium-containing fiber aerogel.
[0008] The third object of the present invention is to provide the application of the above-mentioned zirconium-containing fiber aerogel in the fields of filtration, sound absorption, heat insulation and thermal insulation under a temperature environment of -196 to 1300°C.
[0009] The technical solution for achieving the above-mentioned invention object can be summarized as follows:
[0010] The zirconium-containing fiber aerogel having an isotropic pore structure comprises the following components in parts by weight:
[0011] Contains 0.2-10 parts of zirconium fiber, 0.3-0.5 parts of foaming agent, 0.3-1.0 parts of foam stabilizer and / or 0.3-1.0 parts of dispersant, and 3-50 parts of reinforcing agent.
[0012] According to the present invention, preferably, the zirconium-containing fiber is a single-component zirconium oxide fiber or a zirconium oxide multiphase fiber with a composite second phase; preferably, the second phase includes one of silicon oxide, aluminum oxide, yttrium oxide, and lanthanum oxide, and in the zirconium oxide multiphase fiber, the molar content of zirconium oxide is ≥50%, and further preferably, the molar content of zirconium oxide is 90%-70%.
[0013] According to the present invention, preferably, the length of the zirconium-containing fiber is 100-400 μm, more preferably 100-200 μm.
[0014] According to the present invention, preferably, the type of the foaming agent is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfate, sodium alkyl ether sulfate, alkyl polysaccharide, polyvinyl alcohol, Tween 20, tea saponin, fatty acid soap, alkyl ammonium oxide, α-amino acid or a combination thereof.
[0015] According to the present invention, preferably, the foam stabilizer and the dispersant are the same or different substances, selected from one or a combination of polyvinyl alcohol, hydroxypropyl methylcellulose, polyacrylamide, polyethyleneimine, and maltodextrin.
[0016] According to the present invention, preferably, the reinforcing agent is one of MTMS-based silica sol, TEOS-based silica sol, aluminum sol, aluminum borosilicate sol, aluminum dihydrogen phosphate, zirconium oxide sol or a combination thereof.
[0017] According to the present invention, preferably, the zirconium-containing fiber aerogel having an isotropic pore structure comprises the following components in parts by weight:
[0018] Contains 0.5-8 parts of zirconium fiber, 0.3-0.5 parts of foaming agent, 0.4-0.8 parts of foam stabilizer, and 4-30 parts of reinforcing agent.
[0019] According to the present invention, the method for preparing the zirconium-containing fiber aerogel having an isotropic pore structure comprises the following steps:
[0020] (1) weighing zirconium-containing fibers, adding them to a solvent, and chopping and dispersing them to obtain a fiber dispersion;
[0021] (2) adding a foaming agent, a foam stabilizer and / or a dispersant, and a reinforcing agent to the fiber dispersion, and mixing the mixture to obtain a pre-foamed slurry;
[0022] (3) physically foaming the pre-foamed slurry to obtain a fiber foam slurry;
[0023] (4) forming the fiber foam slurry into a mold, using freeze solidification to obtain a solidified fiber foam slurry, and drying to remove the solvent to obtain a fiber aerogel precursor;
[0024] (5) The fiber aerogel precursor is heat-treated to obtain a zirconium-containing fiber aerogel having an isotropic pore structure.
[0025] According to the present invention, preferably, in step (1): the mass concentration of the zirconium-containing fiber in the solvent is 0.2%-10%, preferably, the mass concentration of the zirconium-containing fiber in the solvent is 0.2%-8%; further preferably, the mass concentration of the zirconium-containing fiber in the solvent is 1%-5%;
[0026] Preferably, the chopped and dispersed fibers are achieved by using a device in which a centrifugal motor drives a cutting blade. After chopped fibers, the length of the fibers is 100-400 μm. Preferably, the length of the fibers is 100-200 μm.
[0027] According to the present invention, preferably, in step (1), the solvent is water.
[0028] According to the present invention, preferably, in step (2): the amount of the foaming agent added is 0.3%-0.5% relative to the mass of the fiber dispersion;
[0029] Preferably, the amount of the foam stabilizer or dispersant added is 0.3%-1.0% relative to the mass of the fiber dispersion liquid, and further preferably, the amount of the dispersant added is 0.3%-0.8%;
[0030] Preferably, the amount of the reinforcing agent added is 3%-50% relative to the mass of the fiber dispersion, and further preferably, the amount of the reinforcing agent added is 3%-25%.
[0031] According to the present invention, preferably, in step (3): the physical foaming method is achieved by stirring, and the stirring speed is 1200-3800r / min, and further preferably, the stirring speed is 2000-3500r / min;
[0032] Preferably, the stirring time is 3-10 min, and further preferably, the stirring time is 5-10 min.
[0033] According to the present invention, preferably, in step (3): during the stirring and foaming process, the final material density is controlled by the expansion volume of the fiber slurry, and the volume expansion of the obtained fiber foam slurry is controlled to be 1.5 times to 3 times of the original volume.
[0034] According to the present invention, preferably, in step (4): the freezing solidification is performed in an environment of -40°C to -80°C, and more preferably liquid nitrogen is used for the freezing solidification;
[0035] Preferably, the drying method is natural drying, heating drying, freeze drying or supercritical drying.
[0036] According to the present invention, preferably, in step (5): the heat treatment is performed in an air atmosphere, a nitrogen atmosphere or a vacuum atmosphere;
[0037] Preferably, the heat treatment temperature is 500-1200° C., and the heat treatment time is 2-8 hours.
[0038] According to the present invention, the above-mentioned zirconium-containing fiber aerogel is used in the fields of filtration, sound absorption, heat insulation and thermal insulation;
[0039] It is preferably used in a temperature environment of -196 to 1300°C.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. The present invention utilizes foaming technology to prepare fiber aerogel. Compared with the conventional freezing method, an isotropic microstructure can be obtained. At the same time, the size of the material pores can be regulated by changing the foaming parameters to achieve adjustable structure.
[0042] 2. The present invention uses zirconium-containing fibers as structural elements of fiber aerogel, and the fiber aerogel has higher temperature resistance.
[0043] 3. The method used in the present invention for preparing the material is simple and has good uniformity. The raw materials used have low toxicity and are suitable for large-scale and large-scale production.
[0044] 4. The present invention uses a foaming method to construct a porous structure inside the material, which is simple and quick. The obtained material is isotropic and its microstructure can be adjusted to meet various requirements. It has broad application prospects in the fields of high-temperature furnaces, high-speed aircraft, aerospace technology, high-temperature flue gas filtration, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 is an optical photograph of the isotropic pore structure zirconium fiber aerogel obtained in Example 1;
[0046] Figure 2 is a SEM photograph of the isotropic pore structure zirconium fiber aerogel obtained in Example 1;
[0047] Figure 3 This is a picture showing the thermal insulation capability of the isotropic pore structure zirconium fiber aerogel obtained in Example 1 in different directions;
[0048] Figure 4 is a graph of the sound absorption coefficient of the isotropic pore structure zirconium fiber aerogel obtained in Example 1;
[0049] Figure 5 is a thermal conductivity diagram of the isotropic pore structure zirconium fiber aerogel obtained in Example 1;
[0050] Figure 6 is a filtration efficiency diagram of the isotropic pore structure zirconium fiber aerogel obtained in Example 1;
[0051] Figure 7 is the stress-strain diagram of the isotropic pore structure zirconium fiber aerogel obtained in Example 2;
[0052] Figure 8 This is a diagram showing the size change of the isotropic pore structure zirconium fiber aerogel obtained in Example 3 after heat treatment at different temperatures.
[0053] Fig. 9 This is an optical micrograph of the zirconium fiber aerogel without pore structure obtained in Comparative Example 1. Specific implementation methods
[0055] The present invention provides a zirconium-containing fiber aerogel with an isotropic pore structure. First, by using foaming technology, bubbles are introduced into the pre-foamed slurry, and the bubbles are evenly distributed in the slurry, retained after curing, and a porous fiber aerogel is obtained after drying. The size of the pores can be regulated by the foaming process, thereby achieving a modulatable microstructure. When no foam is added, the zirconium-containing fiber aerogel has anisotropic properties; after adding foam, the zirconium-containing fiber aerogel has an isotropic structure. Secondly, by using zirconium-containing fibers as structural elements, the temperature resistance of the material is improved compared to the reported glass fibers and ceramic fibers, and it can be used at higher temperatures.
[0056] The zirconium-containing fiber aerogel with an isotropic pore structure of the present invention comprises the following components in parts by weight:
[0057] Contains 0.2-10 parts of zirconium fiber, 0.3-0.5 parts of foaming agent, 0.3-1.0 parts of foam stabilizer and / or 0.3-1.0 parts of dispersant, and 3-50 parts of reinforcing agent.
[0058] In one or more preferred embodiments, the zirconium-containing fiber is a single-component zirconium oxide fiber or a zirconium oxide multiphase fiber with a composite second phase; preferably, the second phase includes one of silicon oxide, aluminum oxide, yttrium oxide, and lanthanum oxide, and in the zirconium oxide multiphase fiber, the molar content of zirconium oxide is ≥50%, and further preferably, the molar content of zirconium oxide is 90%-70%.
[0059] In one or more preferred embodiments, the length of the zirconium-containing fiber is 100-400 μm, more preferably 100-200 μm.
[0060] In one or more preferred embodiments, the foaming agent is selected from sodium dodecyl sulfate, sodium dodecylbenzene sulfate, sodium alkyl ether sulfate, alkyl polysaccharide, polyvinyl alcohol, Tween 20, tea saponin, fatty acid soap, alkyl ammonium oxide, α-amino acid, or a combination thereof.
[0061] According to the present invention, the foam stabilizer and dispersant can ensure that the foam will not be destroyed and the fibers will not be deposited during the curing process, and the two can be the same substance.
[0062] In one or more preferred embodiments, the foam stabilizer and the dispersant are the same or different substances, selected from polyvinyl alcohol, hydroxypropyl methylcellulose, polyacrylamide, polyethyleneimine, maltodextrin or a combination thereof.
[0063] According to the invention, the reinforcing agent imparts strength to the material at high temperatures.
[0064] In one or more preferred embodiments, the reinforcing agent is one of MTMS-based silica sol, TEOS-based silica sol, aluminum sol, aluminum borosilicate sol, aluminum dihydrogen phosphate, zirconium oxide sol, or a combination thereof.
[0065] In one or more preferred embodiments, the zirconium-containing fiber aerogel having an isotropic pore structure comprises the following components in parts by weight:
[0066] Contains 0.5-8 parts of zirconium fiber, 0.3-0.5 parts of foaming agent, 0.4-0.8 parts of foam stabilizer, and 4-30 parts of reinforcing agent.
[0067] According to the present invention, the method for preparing the zirconium-containing fiber aerogel having an isotropic pore structure comprises the following steps:
[0068] (1) weighing zirconium-containing fibers, adding them to a solvent, and chopping and dispersing them to obtain a fiber dispersion;
[0069] (2) adding a foaming agent, a foam stabilizer and / or a dispersant, and a reinforcing agent to the fiber dispersion, and mixing the mixture to obtain a pre-foamed slurry;
[0070] (3) physically foaming the pre-foamed slurry to obtain a fiber foam slurry;
[0071] (4) forming the fiber foam slurry into a mold, using freeze solidification to obtain a solidified fiber foam slurry, and drying to remove the solvent to obtain a fiber aerogel precursor;
[0072] (5) The fiber aerogel precursor is heat-treated to obtain a zirconium-containing fiber aerogel having an isotropic pore structure.
[0073] In one or more preferred embodiments, in step (1): the mass concentration of the zirconium-containing fiber in the solvent is 0.2%-10%, preferably, the mass concentration of the zirconium-containing fiber in the solvent is 0.2%-8%; further preferably, the mass concentration of the zirconium-containing fiber in the solvent is 1%-5%;
[0074] Preferably, the chopped and dispersed fibers are achieved by using a device in which a centrifugal motor drives a cutting blade. After chopped fibers, the length of the fibers is 100-400 μm. Preferably, the length of the fibers is 100-200 μm.
[0075] In one or more preferred embodiments, in step (1), the solvent is water.
[0076] In one or more preferred embodiments, in step (2): the amount of the foaming agent added is 0.3%-0.5% relative to the mass of the fiber dispersion;
[0077] Preferably, the amount of the foam stabilizer or dispersant added is 0.3%-1.0% relative to the mass of the fiber dispersion liquid, and further preferably, the amount of the dispersant added is 0.3%-0.8%;
[0078] Preferably, the amount of the reinforcing agent added is 3%-50% relative to the mass of the fiber dispersion, and further preferably, the amount of the reinforcing agent added is 3%-25%.
[0079] In one or more preferred embodiments, in step (3): the physical foaming method is achieved by stirring, and the stirring speed is 1200-3800 r / min, and further preferably, the stirring speed is 2000-3500 r / min;
[0080] Preferably, the stirring time is 3-10 min, and further preferably, the stirring time is 5-10 min.
[0081] According to the present invention, in step (3): during the stirring and foaming process, the final material density is controlled by the expansion volume of the fiber slurry.
[0082] In one or more preferred embodiments, the volume expansion of the fiber foam slurry is controlled to be 1.5 to 3 times of the original volume.
[0083] According to the present invention, in step (4): for a fiber foam slurry, the mold molding can be directly placed in the mold for curing to obtain a cured fiber foam slurry; for multiple fiber foam slurries, they can be combined into a whole by multiple curing methods to obtain a cured fiber foam slurry with a multi-level structure.
[0084] In one or more preferred embodiments, the cryosolidification is performed in an environment of -40°C to -80°C, preferably using liquid nitrogen for cryosolidification;
[0085] Preferably, the drying method is natural drying, heating drying, freeze drying or supercritical drying.
[0086] In one or more preferred embodiments, in step (5): the heat treatment is performed in an air atmosphere, a nitrogen atmosphere, or a vacuum atmosphere;
[0087] Preferably, the heat treatment temperature is 500-1200° C., and the heat treatment time is 2-8 hours.
[0088] According to the present invention, the above-mentioned zirconium-containing fiber aerogel is used in the fields of filtration, sound absorption, heat insulation and thermal insulation;
[0089] It is preferably used in a temperature environment of -196 to 1300°C.
[0090] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.
[0091] Example 1.
[0092] Weigh 4g of zirconium oxide fiber, add it to 100g of deionized water, use a homogenizer to homogenize and disperse the fibers at 8000rpm, and the obtained fiber length is about 200μm. Add 0.3% of hydroxypropyl methylcellulose as a dispersant and foam stabilizer to the dispersed mixed solution, add 25% of MTMS-based silica sol as a reinforcing agent to the dispersed mixed solution, and add 0.5% of tea saponin as a foaming agent to the dispersed mixed solution. After mixing evenly, stir at 2000rpm for 5min to obtain a stable fiber foam slurry. Pour the obtained fiber foam slurry into a 50*50*50mm mold, freeze-solidify at -80℃, dry the material by freeze-drying, and heat-treat the dried sample at 900℃ in an air atmosphere for 1 hour to obtain a zirconium-containing fiber aerogel with an isotropic pore structure.
[0093] The optical photograph of the zirconium-containing fiber aerogel with isotropic pore structure prepared in this example is as follows: Figure 1 As shown; SEM photos as Figure 2As shown; the thermal insulation capacity in different directions is as Figure 3 As shown; the sound absorption performance is as Figure 4 As shown; high temperature thermal conductivity is as Figure 5 As shown; air filtration performance as Figure 6 shown.
[0094] Depend on Figure 2 It can be seen that there are very obvious nearly circular holes inside the material;
[0095] Depend on Figure 3 It can be seen that the material has similar temperature distribution when heated in three directions, which indicates that the thermal insulation performance of the material in three directions is similar, which further illustrates the isotropy of the material structure;
[0096] Depend on Figure 4 It can be seen that the material has good sound absorption performance at low frequencies, and the noise reduction coefficient is 0.47;
[0097] Depend on Figure 5 It can be seen that the material has a low thermal conductivity at each temperature point;
[0098] Depend on Figure 6 It can be seen that the filtration efficiency of the material for particles of different sizes is above 90%, and the filtration efficiency for particles of 3.0 μm, 5.0 μm and 10.0 μm reaches 100%.
[0099] Example 2.
[0100] Weigh 6g of zirconium oxide fiber and add it to 100g of deionized water. The mass ratio of fiber to solvent in the obtained mixed solution is 6%. Use a homogenizer to homogenize and disperse the fiber at 8000rpm. The obtained fiber length is about 200μm. Add 0.3% of hydroxypropyl methylcellulose as a dispersant and foam stabilizer to the dispersed mixed solution, add 25% of MTMS-based silica sol as a reinforcing agent to the dispersed mixed solution, and add 0.5% of tea saponin as a foaming agent to the dispersed mixed solution. The agent is mixed evenly and stirred at a speed of 2000 rpm for 5 minutes to obtain a stable fiber foam slurry, the obtained fiber foam slurry is poured into a 50*50*50 mm mold, and freeze-cured at a temperature of -80°C. The material is dried by a freeze-drying method, and the dried sample is heat-treated at a temperature of 900°C for 1 hour to obtain a modulatable zirconium-containing fiber aerogel. The obtained zirconium-containing fiber aerogel with an isotropic pore structure has a higher density and better mechanical properties.
[0101] The stress-strain diagram of the zirconium-containing fiber aerogel with isotropic pore structure prepared in this example is shown in FIG. Figure 7 shown.
[0102] Depend on Figure 7It can be seen that the stress-strain curve of the material is continuous and smooth, indicating that there is no brittle fracture and the material is flexibly deformed.
[0103] Example 3.
[0104] 4 g of zirconium oxide fiber was weighed and added to 100 g of deionized water. The mass ratio of fiber to solvent in the obtained mixed solution was 4%. The fiber was homogenized and dispersed at 8000 rpm using a homogenizer. The obtained fiber length was about 200 μm. Hydroxypropyl methylcellulose was added to the dispersed mixed solution at an amount of 0.3% as a dispersant and foam stabilizer, MTMS-based silica sol was added to the dispersed mixed solution at an amount of 25% as a reinforcing agent, and tea saponin was added to the dispersed mixed solution at an amount of 0.5% as a foaming agent. After mixing evenly, stir at a speed of 2000rpm for 5min to obtain a stable fiber foam slurry, pour the obtained fiber foam slurry into a 50*50*50mm mold, freeze-solidify at a temperature of -80℃, and dry the material by freeze-drying. The dried samples are heat treated at 900℃, 1000℃, 1100℃, 1200℃ and 1300℃ for one hour respectively, and the size of the zirconium-containing fiber aerogel with an isotropic pore structure is basically the same.
[0105] The size changes of the zirconium-containing fiber aerogel with isotropic pore structure prepared in this example after heat treatment at different temperatures are as follows: Figure 8 shown.
[0106] Depend on Figure 8 It can be seen that the size of the material does not change substantially after heat treatment at different temperatures, and the structural stability can be maintained at high temperatures.
[0107] Comparative Example 1.
[0108] As described in Example 1, except that:
[0109] Without adding a foaming agent or performing a foaming operation, the obtained fiber suspension was poured into a 50*50*50mm mold, frozen and solidified at a temperature of -80°C, and the material was dried by freeze drying. The dried sample was heat treated at 900°C in an air atmosphere for 1 hour to obtain a zirconium-containing fiber aerogel with a pore-free structure. As a result, because there was no bubble support for the fiber framework, the growing fibers of the ice crystals had a significant repulsive effect, forming a distinct layered structure.
[0110] The optical micrograph of the zirconium fiber aerogel without pore structure prepared in this comparative example is as follows: Fig. 9 shown.
[0111] Depend on Fig. 9It can be seen that the sample obtained by foaming without adding a foaming agent does not have an isotropic pore structure, but has an anisotropic layered structure.
Claims
1. A zirconium-containing fiber aerogel having an isotropic pore structure, characterized in that: The zirconium-containing fiber aerogel comprises the following components in parts by weight: Contains 0.2-10 parts of zirconium fiber, 0.3-0.5 parts of foaming agent, 0.3-1.0 parts of foam stabilizer and / or 0.3-1.0 parts of dispersant, and 3-50 parts of reinforcing agent.
2. The zirconium-containing fiber aerogel with an isotropic pore structure according to claim 1, characterized in that: The zirconium-containing fiber is a single-component zirconium oxide fiber or a zirconium oxide multiphase fiber with a composite second phase; preferably, the second phase includes one of silicon oxide, aluminum oxide, yttrium oxide, and lanthanum oxide, and in the zirconium oxide multiphase fiber, the molar content of zirconium oxide is ≥50%.
3. The zirconium-containing fiber aerogel with an isotropic pore structure according to claim 1, characterized in that: The length of the zirconium-containing fibers is 100-400 μm.
4. The zirconium-containing fiber aerogel with an isotropic pore structure according to claim 1, characterized in that: The foaming agent is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfate, sodium alkyl ether sulfate, alkyl polysaccharide, polyvinyl alcohol, Tween 20, tea saponin, fatty acid soap, alkyl ammonium oxide, α-amino acid or a combination thereof; Preferably, the foam stabilizer and the dispersant are the same or different substances, selected from polyvinyl alcohol, hydroxypropyl methylcellulose, polyacrylamide, polyethyleneimine, maltodextrin or a combination thereof; Preferably, the reinforcing agent is one of MTMS-based silica sol, TEOS-based silica sol, aluminum sol, aluminum borosilicate sol, aluminum dihydrogen phosphate, zirconium oxide sol or a combination thereof.
5. The zirconium-containing fiber aerogel with an isotropic pore structure according to claim 1, characterized in that: The zirconium-containing fiber aerogel having an isotropic pore structure comprises the following components in parts by weight: Contains 0.5-8 parts of zirconium fiber, 0.3-0.5 parts of foaming agent, 0.4-0.8 parts of foam stabilizer, and 4-30 parts of reinforcing agent.
6. The method for preparing the zirconium-containing fiber aerogel having an isotropic pore structure according to any one of claims 1 to 5, comprising the following steps: (1) weighing zirconium-containing fibers, adding them to a solvent, and chopping and dispersing them to obtain a fiber dispersion; (2) adding a foaming agent, a foam stabilizer and / or a dispersant, and a reinforcing agent to the fiber dispersion, and mixing the mixture to obtain a pre-foamed slurry; (3) physically foaming the pre-foamed slurry to obtain a fiber foam slurry; (4) forming the fiber foam slurry into a mold, using freeze solidification to obtain a solidified fiber foam slurry, and drying to remove the solvent to obtain a fiber aerogel precursor; (5) The fiber aerogel precursor is heat-treated to obtain a zirconium-containing fiber aerogel having an isotropic pore structure.
7. The method for preparing the zirconium-containing fiber aerogel having an isotropic pore structure according to claim 6, characterized in that: In step (1): the mass concentration of the zirconium-containing fiber in the solvent is 0.2%-8%; preferably, the mass concentration of the zirconium-containing fiber in the solvent is 1%-5%; Preferably, the chopped and dispersed fibers are achieved by using a centrifugal motor to drive a cutting blade; Preferably, the solvent is water.
8. The method for preparing the zirconium-containing fiber aerogel having an isotropic pore structure according to claim 6, characterized in that: In step (3): the physical foaming method is achieved by stirring, and the stirring speed is 1200-3800 r / min, preferably, the stirring speed is 2000-3500 r / min; Preferably, during the stirring and foaming process, the volume expansion of the fiber foam slurry is controlled to be 1.5 to 3 times of the original volume.
9. The method for preparing zirconium-containing fiber aerogel having an isotropic pore structure according to claim 6, characterized in that: In step (4): the freezing and solidification is carried out in an environment of -40°C to -80°C; Preferably, the drying method is natural drying, heating drying, freeze drying or supercritical drying; Preferably, in step (5): the heat treatment is performed in an air atmosphere, a nitrogen atmosphere or a vacuum atmosphere; Preferably, the heat treatment temperature is 500-1200° C., and the heat treatment time is 2-8 hours.
10. Application of the zirconium-containing fiber aerogel according to any one of claims 1 to 5 in the fields of filtration, sound absorption, heat insulation and thermal insulation; It is preferably used in a temperature environment of -196 to 1300°C.
Citation Information
Patent Citations
Elastic ceramic nanofiber aerogel and preparation method and use thereof
CN109180213A
Method for preparing zirconium dioxide aerogel with different microtopographies
CN114772637A
Silica fiber aerogel and preparation method thereof
CN115286357A
Preparation method of glass fiber aerogel
CN115850786A
Ceramic fiber aerogel as well as preparation method and application thereof
CN118147788A